Method for preparing CON framework type molecular sieve
By using 1,2,3,4,6,7,8,9- octopus and hydrogeniazine and [1,2-A] ionazole-10-cation as a structural orientation, simplified the synthesis process of the Constorbial molecular sieve , Solve the problem of complexity and cost in existing technologies, and realize the preparation of high -efficiency and low -cost molecular sieve materials.
Patent Information
- Application Number
- CN202380047316.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the synthesis process of molecular sieve such as CON skeleton type is complicated, has high cost, and it is difficult to obtain efficient structural guides at low cost.
Use 1,2,3,4,7,7,8,9- and eight-hydrogeniazine and [1,2-A] ionazole-10-cation as a structural orientation agent, with simple synthetic methods from 100 ° C to 200 Correctize at the temperature of ° C to form a Cononal sieve of the CON skeleton type.
It simplifies the synthesis process of CON framework materials, reduces costs, and improves the hydrothermal stability and Si/Al ratio of the material in the presence of fluoride ions, making it suitable for low-acidity catalytic applications.
Smart Images

Figure CN119365419A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 359,255, filed on July 8, 2022, which is incorporated herein by reference in its entirety. Technical Field
[0003] The present disclosure relates to a method for preparing a CON framework type molecular sieve using a novel structure directing agent, and also relates to a molecular sieve material obtained by the method and to a molecular sieve material containing the structure directing agent in its pore structure. Background Art
[0004] Both natural and synthetic molecular sieve materials can be used as adsorbents and have catalytic properties to hydrocarbon conversion reactions. Specific molecular sieves such as zeolites, AlPO and mesoporous materials are ordered porous crystalline materials with clear crystal structures as determined by X-ray diffraction (XRD). Specific molecular sieves are ordered and produce clear and recognizable XRD patterns. In a specific molecular sieve material, there can be a large number of cavities that can be interconnected by many channels or holes. In a specific molecular sieve material, the size of these cavities and holes is uniform. Because the size of these holes can accept adsorbed molecules of a specific size, molecules of larger size are not accepted simultaneously, so these materials are called "molecular sieves", and are used in a variety of industrial processes, for example, cracking, hydrocracking, disproportionation, alkylation, oligomerization and isomerization.
[0005] Molecular sieves used in catalysis and adsorption include any naturally occurring or synthesized crystalline molecular sieves. Examples of these molecular sieves include ultra-large pore zeolites, large pore zeolites, medium pore size zeolites and small pore zeolites. These zeolites and their isotypes are classified by the International Zeolite Association Structure Committee according to the rules of the IUPAC Committee on zeolite naming. According to this classification, the framework zeolites and other crystalline microporous molecular sieves that have established their structure are given three letter codes, and are described in " Zeolite Framework Types Collection (Atlas of Zeolite Framework Types) " edited by Ch.Baerlocher, LBM McCusker and DH Olson, Elsevier, the 6th edition, in 2007, the publication is incorporated herein by reference. These zeolites and their isotypes are also described in the Zeolite Structure Database, which provides the structural information of all zeolite framework types approved by the International Zeolite Association Structure Committee (IZA-SC).
[0006] The ideal inorganic framework structure of zeolite is the framework of silicate, wherein all tetrahedral atoms are connected with the tetrahedral atoms of four next nearest neighbors by oxygen atoms. As used herein, term " silicate " refers to a kind of material, it contains at least silicon and oxygen atoms (that is, -O-Si-O-Si-) that are bonded alternately to each other, and optionally comprises other atoms in inorganic framework structure, including atom such as boron, aluminum or other metal (for example, transition metal such as titanium, vanadium or zinc). The atom except silicon and oxygen in framework silicate occupies a part of the lattice site originally occupied by silicon atom in " full-silicon dioxide " framework silicate. Therefore, as used herein, term " framework silicate " refers to the atomic lattice comprising any one in silicate, borosilicate, gallosilicate, ferrosilicate, aluminosilicate, titanosilicate, zinc silicate, vanadosilicate etc.
[0007] The structure of the framework silicate in a given zeolite determines the size of the pores or channels present therein. The pore or channel size can determine the type of process for which a given zeolite is applicable. Currently, more than 200 unique zeolite framework silicate structures are known and recognized by the International Zeolite Association Structure Committee, thereby defining the range of pore geometries and orientations.
[0008] The framework silicate of a zeolite or molecular sieve is usually characterized by its ring size, where the ring size refers to the number of silicon atoms (or substituted atoms, such as those listed above) that are tetrahedrally coordinated with oxygen atoms in one loop to define pores or channels in the interior of the zeolite. For example, an "8-ring" zeolite refers to a zeolite having pores or channels defined by 8 alternating tetrahedral atoms and 8 oxygen atoms in one loop. The pores or channels defined in a given zeolite can be symmetrical or asymmetrical, depending on the various structural constraints present in a particular framework silicate.
[0009] Zeolites can be classified as having small, medium, large and ultra-large pore structures, with pore windows defined by 8, 10, 12 and more than 12 T atoms, respectively. Ultra-large pore zeolites (>12R) include, for example, AET (14R, such as ALPO-8), SFN (14R, such as SSZ-59), VFI (18R, such as VPI-5), CLO (20R, such as cloverite) and ITV (30R, such as ITQ-37) framework zeolites. The free pore size of ultra-large pore zeolites is generally greater than about 0.8 nm. Large pore zeolites (12R) include, for example, LTL, MAZ, FAU, EMT, OFF, *BEA and MOR framework zeolites, for example, pyrite, pyroxenite, zeolite L, zeolite Y, zeolite X, omega, ZSM-2, zeolite T and β (Βeta). The free pore size of large pore zeolites is generally 0.6 nm to 0.8 nm. Medium (or intermediate) pore size zeolites (10R) include, for example, MFI, MEL, EUO, MTT, MFS, AEL, AFO, HEU, FER, MWW and TON framework zeolites, for example, ZSM-5, ZSM-11, ZSM-22, MCM-22, silicalite-1 and silicalite-2. The free pore size of medium pore size zeolites is generally 0.45 nm to 0.6 nm. Small pore size zeolites (8R) include, for example, CHA, RTH, ERI, KFI, LEV and LTA framework type zeolites, for example, ZK-4, SAPO-34, SAPO-35, ZK-14, SAPO-42, ZK-21, ZK-22, ZK-5, ZK-20, zeolite A, chabazite and ALPO- 17. The free pore size of small pore size zeolites is typically 0.3 nm to 0.45 nm.
[0010] The synthesis of molecular sieve materials generally involves hydrothermal crystallization from a synthesis mixture containing sources of all elements present in the molecular sieve (or zeolite), such as a source of silicon dioxide and a source of aluminum oxide, etc. In many cases, a structure directing agent (SDA) is also present. A structure directing agent is a compound that is believed to promote the formation of a molecular sieve and is believed to serve as a template around which a specific molecular sieve structure can be formed and thereby promote the formation of the desired molecular sieve. A variety of compounds have been used as structure directing agents, including various types of quaternary ammonium cations. Typically, once crystallization is complete, molecular sieve (or zeolite) crystals will form around the structure directing agent, wherein the structure directing agent occupies the pores in the molecular sieve. Therefore, the "as-synthesized" (or "as-made") molecular sieve will contain a structure directing agent in its pores, so that after crystallization, the "as-synthesized" molecular sieve is generally subjected to a treatment step such as a calcination step to remove the structure directing agent.
[0011] For example, macroporous zeolites include CON framework type zeolites such as aluminosilicate SSZ-26, borosilicate SSZ-33 or borosilicate CIT-1, which are characterized by a three-dimensional pore system composed of intersecting 10-ring and 12-ring pores. Such macroporous materials with intersecting channels are of great interest in catalytic applications, such as in the petrochemical industry. For example, U.S. Patent No. 8,198,501 discloses the use of CON-type zeolites to catalyze the isomerization of light paraffins. Such macroporous materials with intersecting channels are also considered to have increased fouling resistance and enhanced intracrystalline diffusion properties compared to materials with one-dimensional channels.
[0012] The SSZ-26 and SSZ-33 materials may be characterized in that they are members of a class of materials in which two end members are formed by stacking layers in an ABAB sequence (“polymorph A”) or an ABCABC sequence (“polymorph B”). Between these end member polymorphs, there is a whole class of materials (“SSZ-26 / 33 class”) whose characteristics may lie in that the stacking fault probability “p” is 0% < p < 100%. If the stacking fault probability is p = 0%, the end member polymorph B is obtained, and if p = 100%, the end member polymorph A is obtained. SSZ-26 and SSZ-33 are members of this disordered class of materials. More particularly, SSZ-33 and SSZ-26 are symbiotes of polymorphs A and B, where polymorph B predominates, and the stacking fault probabilities are close to 30% and 15% respectively. The SSZ-26 and SSZ-33 materials were first synthesized using hexamethyl[4.3.3.0]propellane-8,11-diammonium cations or tricyclo[5.2.1.0 2,6 decane quaternary ammonium cations as structure directing agents (SDA). See, for example, Lobo et al., “SSZ-26 and SSZ-33: Two Molecular Sieves with Intersecting 10-and 12-Ring Pores”, Science, Vol. 262(5139), pp. 1543-1546, December 3, 1993; U.S. Patent No. 4,910,006; U.S. Patent No. 4,963,337; U.S. Patent No. 5,007,997. Zeolites of the SSZ-26 / 33 class are also synthesized from a variety of SDAs, such as 1,5-bis(N,N-dimethylcyclohexylammonium)pentane divalent cations, 1,4-bis(N-cyclohexylpiperidine )butane divalent cations, 1,4-bis(N-cyclopentylpiperidine )butane divalent cations or 1-benzyl-4-aza-1-az -bicyclo[2.2.2]octane (see, e.g., U.S. Pat. Nos. 7,648,694 and 10,730,757), U.S. Pat. No. 8,647,601 describes the use of 1,1'-(pentane-1,5-diyl)bis(3-methylcyclohexyl)piperidine Divalent cations are used as SDA to synthesize SSZ-33; U.S. Patent No. 7,837,978 describes a method for directly preparing aluminum-containing molecular sieve SSZ-26, which uses cis-N,N-diethyldecahydroquinoline Cationic or cis-N,N-diethyldecahydroquinoline Cation and trans-N,N-diethyldecahydroquinoline mixture of cations as SDA; and U.S. Pat. No. 10,189,717 describes the presence of 1,4-bis(N-cyclohexylpyrrolidine ) When butane divalent cation is used as SDA, aluminosilicate SSZ-26 is synthesized by interzeolite conversion of FAU framework-type zeolite.
[0013] CIT-1 corresponds to pure or nearly pure polymorph B and has been synthesized using N,N,N-trimethyl-(-)-cis-myrtylammonium hydroxide as SDA. See, e.g., Lobo et al., "CIT-1: A New Molecular Sieve with Intersecting Pores Bounded by 10-and 12-Rings," J. Am. Chem. Soc, Vol. 117, pp. 3766-3779, 1995.
[0014] Despite these advances, there remains a need for new structure directing agents and more efficient methods for the synthesis of molecular sieves, such as CON framework-type molecular sieves, particularly lower cost alternatives.
[0015] In accordance with the present disclosure, it has now been discovered that the relatively simple cations described herein can effectively serve as structure directing agents in the synthesis of molecular sieves or zeolites of the CON framework type. Summary of the invention
[0016] According to the present disclosure, it has been discovered that 1,2,3,4,6,7,8,9-octahydropyridazin[1,2-a]indazole-10- The cation can be suitably used as a molecular sieve (or zeolite) for preparing a CON framework type, including a structure directing agent (SDA) for directly synthesizing aluminum-containing molecular sieves such as aluminosilicates and aluminoborosilicates of a CON framework type. Since the SDA can be manufactured in a single step, the synthesis of CON framework type materials is significantly simplified compared to the prior art process using a more complex SDA, so this is particularly advantageous. In addition, the SDA allows the preparation of a CON framework type molecular sieve in the presence of fluoride ions. It can be advantageous to make a zeolite in the presence of fluoride ions because it can obtain fewer hydrophilic silanol (Si-OH) defects compared to zeolites prepared by a hydroxide path, thereby providing higher hydrothermal stability. In addition, a higher Si / Al ratio can be obtained in the presence of fluoride ions, which can be beneficial when lower acidity is required, for example, in hydroisomerization.
[0017] In a first aspect, the present disclosure relates to a method for preparing a molecular sieve of CON framework type, the method comprising the following steps: (a) preparing a synthesis mixture, the synthesis mixture comprising water, a source of silicon dioxide, a source of aluminum oxide, a structure directing agent (Q), a mineralizer, and optionally a source of an alkali metal and / or alkaline earth metal element (M), wherein the mineralizer is selected from hydroxide ions (OH), fluoride ions (F) and mixtures thereof, and wherein the structure directing agent (Q) comprises 1,2,3,4,6,7,8,9-octahydropyridazin[1,2-a]indazole-10-of Formula 1 cation:
[0018]
[0019] (b) heating the synthesis mixture under crystallization conditions including a temperature of 100°C to 200°C for a time sufficient to form crystals of the molecular sieve; and (c) recovering at least a portion of the molecular sieve from step (b).
[0020] In a second aspect, the present disclosure relates to a molecular sieve (or zeolite), in particular a molecular sieve (or zeolite) of CON framework type, wherein the molecular sieve (or zeolite) has at least one 1,2,3,4,6,7,8,9-octahydropyridazine[1,2-a]indazole-10- cation.
[0021] In another aspect, the present disclosure relates to a CON framework-type molecular sieve, which is obtainable by (or is obtained by) the method disclosed herein.
[0022] These and other features and properties of the present disclosure and their advantageous applications and / or uses will be apparent from the following detailed description. Of course, it should be understood that the features described with respect to one aspect of the present invention may be incorporated into other aspects of the present invention. In particular, any two or more features in this specification, including the features described in the Summary of the Invention, may be combined to form a feature combination not specifically described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The powder XRD pattern of the as-synthesized material of Example 2 is shown.
[0024] Figure 2 An SEM image of the as-synthesized product of Example 2 is shown.
[0025] Figure 3 An SEM image of the as-synthesized product of Example 4 is shown.
[0026] Figure 4 The powder XRD pattern of the as-synthesized material of Example 11 is shown.
[0027] Figure 5 The powder XRD pattern of the calcined material of Example 11 is shown.
[0028] Figure 6 The powder XRD pattern of the as-synthesized material of Example 12 is shown. DETAILED DESCRIPTION
[0029] In a first aspect, the present disclosure relates to a method for preparing a molecular sieve of CON framework type, the method comprising the following steps:
[0030] (a) preparing a synthesis mixture comprising water, a source of silicon dioxide, a source of aluminum oxide, a structure directing agent (Q), a mineralizer and optionally a source of an alkali metal and / or alkaline earth metal element (M),
[0031] wherein the mineralizer is selected from hydroxide ions (OH), fluoride ions (F) and mixtures thereof, and
[0032] The structure directing agent (Q) comprises 1,2,3,4,6,7,8,9-octahydropyridazine[1,2-a]indazole-10- cation:
[0033]
[0034] (b) heating the synthesis mixture under crystallization conditions comprising a temperature of 100° C. to 200° C. for a time sufficient to form crystals of the molecular sieve; and
[0035] (c) recovering at least a portion of the molecular sieve from step (b).
[0036] The structure directing agent (Q) may be present in any suitable form, for example as a halide such as a fluoride, chloride, iodide or bromide, as a hydroxide or as a nitrate, for example in the form of its hydroxide. The structure directing agent (Q) may be present in the synthesis mixture in a Q / Si molar ratio of 0.01 to 1.0, for example 0.05 to 1.0, or 0.05 to 0.8, or 0.1 to 0.7, for example 0.05 to 0.1 or 0.15 to 0.5, for example 0.15 or 0.2.
[0037] The synthesis mixture includes at least one source of silicon dioxide. Suitable sources of silicon dioxide (e.g., silicon oxide sources) include silicates, such as tetraalkyl orthosilicates such as tetramethyl orthosilicate (TMOS) and tetraethyl orthosilicate (TEOS), fumed silica such as (available from Evonik), (available from Cabot) and (available from DMS), precipitated silica such as and 340 (available from Evonik), alkali metal silicates such as potassium silicate and sodium silicate, and aqueous colloidal suspensions of silicon dioxide such as those sold by EI du Pont de Nemours under the trade name Sold or marketed by Evonik under the trade name Those which are commercially available; preferably silicates, fumed silica, precipitated silica, alkali metal silicates, especially colloidal silica and tetraalkyl orthosilicates such as TEOS.
[0038] The synthesis mixture contains at least one source of aluminum oxide. Suitable sources of aluminum oxide (e.g., aluminum oxide sources) include aluminum hydroxide, aluminum salts, especially water-soluble salts, such as aluminum sulfate, aluminum nitrate, alkali metal aluminates such as sodium aluminate, and aluminum alkoxides such as aluminum isopropoxide, and hydrated aluminum oxides such as boehmite, gibbsite and pseudoboehmite, and mixtures thereof. Other aluminum sources include, but are not limited to, other water-soluble aluminum salts, sodium aluminate, aluminum alkoxides such as aluminum isopropoxide, or aluminum metal such as aluminum in the form of fragments. Particularly suitable sources of aluminum oxide are aluminum hydroxide and water-soluble salts such as aluminum sulfate, aluminum nitrate, and alkali metal aluminates such as sodium aluminate and potassium aluminate.
[0039] Instead of or in addition to the previously mentioned sources of Si and Al, a source containing both Si and Al elements may be used. Examples of suitable sources containing both Si and Al elements include amorphous silica-alumina gel or dried silica alumina powder, silica alumina, clays such as kaolin, metakaolin, and zeolites, particularly aluminosilicates, such as synthetic faujasite and ultrastable faujasite such as Ultrastable Y (USY), β or other large to medium pore molecular sieves or zeolites.
[0040] The Si / Al molar ratio of the synthesis mixture may be 5 to 100, such as 5 to 75, such as 10 to 50, or 10 to 35, such as 10, 15, 20, 25, 30 or 35.
[0041] The synthesis mixture can also optionally include at least one source of boron oxide, such as boric acid and borates such as sodium tetraborate or at least one of borax and potassium tetraborate. In hydroxide-mediated synthesis systems, the source of boron tends to be more soluble than the source of aluminum. In embodiments in which the synthesis mixture includes boron, the molecular sieve is aluminoborosilicate, and boron can be present in the synthesis mixture with a Si / B molar ratio of 5 to 100, such as 5 to 75, such as 10 to 50, or 10 to 35, such as 10, 15, 20, 25, 30 or 35. In another embodiment, the Si / [Al+B] molar ratio of the synthesis mixture can be 5 to 100, such as 5 to 75, such as 10 to 50, or 10 to 35, such as 10, 15, 20, 25, 30 or 35.
[0042] The synthesis mixture comprises at least one mineralizer selected from hydroxide ions (OH), fluoride ions (F) and mixtures thereof. The content of the mineralizer expressed as a (OH+F) / Si molar ratio of the synthesis mixture may be from 0.05 to 1.5, most typically from 0.1 to 1.0, such as from 0.15 or from 0.2 to 1.0.
[0043] When the mineralizer comprises hydroxide ions (OH), the synthesis mixture comprises at least one source of hydroxide ions (OH). For example, hydroxide ions may be present as counterions of the structure directing agent (Q), or by using aluminum hydroxide or sodium aluminate as a source of aluminum oxide. Suitable sources of hydroxide ions may also be selected from alkali metal hydroxides, alkaline earth metal hydroxides, ammonium hydroxides and mixtures thereof; for example, selected from sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, calcium hydroxide, magnesium hydroxide, ammonium hydroxide and mixtures thereof; more typically selected from sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonium hydroxide and mixtures thereof; most typically selected from sodium hydroxide and / or potassium hydroxide. The synthesis mixture may comprise a source of hydroxide ions in a OH / Si molar ratio of 0.05 to 1.5, such as 0.1 to 1.0, such as 0.15 to 0.7, such as 0.1 or 0.15 to 0.6 or 0.5. When the mineralizer comprises hydroxide ions (OH), the synthesis mixture may be substantially free of fluoride ions (F).
[0044] When the mineralizer comprises fluoride ions (F), the synthesis mixture comprises at least one source of fluoride ions (F). The source of fluoride ions (F) can be any compound capable of releasing fluoride ions in the molecular sieve synthesis mixture. For example, fluoride ions can be present as counterions to the structure directing agent (Q). Non-limiting examples of sources of fluoride ions (F) include hydrogen fluoride (HF); salts containing one or more fluoride ions, such as metal fluorides, preferably wherein the metal is an alkali metal or alkaline earth metal such as sodium, potassium, calcium, magnesium, strontium or barium, or a metal such as aluminum (AlF3, Al2F6) or tin (SnF2); ammonium fluoride (NH4F); and ammonium bifluoride (NH4HF2). Particularly convenient sources of fluoride ions are HF, NH4F and NH4HF2, in particular HF. Small amounts of fluoride ions (F) may also be present as impurities, for example in the source of optional alkali metal or alkaline earth metal cations (M). Fluoride ions (F) may be present in a F / Si molar ratio of 0.05 to 1.5, such as 0.1 to 1.0, such as 0.15 to 0.7, such as 0.1 or 0.15 to 0.6 or 0.5. When the mineralizer comprises fluoride ions (F), the synthesis mixture may also comprise hydroxide ions (OH) or may be substantially free of hydroxide ions (OH), preferably it further comprises hydroxide ions (OH).
[0045] Optionally, the synthesis mixture may contain one or more alkali metal or alkaline earth metal cation (M) source. If M is present, M is preferably selected from sodium, potassium, lithium, rubidium, calcium, magnesium, strontium, barium and mixtures thereof, preferably selected from sodium and / or potassium. The sodium source, when present, may be sodium hydroxide, sodium aluminate, sodium silicate, sodium aluminate, or a sodium salt such as NaCl, NaBr or sodium nitrate. The potassium source, when present, may be potassium hydroxide, potassium aluminate, potassium silicate, a potassium salt such as KCl or KBr or potassium nitrate. The lithium source, when present, may be lithium hydroxide, or a lithium salt such as LiCl, LiBr, LiI, lithium nitrate or lithium sulfate. The rubidium source, when present, may be rubidium hydroxide, or a rubidium salt such as RbCl, RbBr, RbI or rubidium nitrate. The calcium source, when present, may be calcium hydroxide. The magnesium source, when present, may be magnesium hydroxide. The strontium source, when present, may be strontium hydroxide. The barium source, when present, may be barium hydroxide. The alkali or alkaline earth metal cation M may also be present in one or more sources of aluminum oxide or boron oxide such as sodium aluminate, sodium tetraborate, potassium tetraborate, and / or one or more sources of silicon dioxide such as potassium silicate and / or sodium silicate. The source of alkali or alkaline earth metal cation (M) is advantageously soluble in water. The synthesis mixture may include an alkali or alkaline earth metal cation (M) source with an M / Si molar ratio of 0 to 1.0, for example, when M is present, the synthesis mixture may include an alkali or alkaline earth metal cation (M) source with an M / Si molar ratio of 0.01 to 0.5, particularly 0.05 to 0.5, for example 0.05 to 0.2. Alternatively, the synthesis mixture may be substantially free of alkali or alkaline earth metal cations (M). More particularly, in the above-mentioned first embodiment, the synthesis mixture may contain the source of alkali metal or alkaline earth metal cations (M) in a M / Si molar ratio of 0.01 to 1.0, such as 0.01 or 0.05 to 0.5, such as 0.05 or 0.1 to 0.2 or 0.15, while in the above-mentioned second or third embodiments, the synthesis mixture may contain the source of alkali metal or alkaline earth metal cations (M) in such an amount, or more generally be substantially free of alkali metal or alkaline earth metal cations (M).
[0046] The synthesis can be carried out with or without added nucleating seeds. If nucleating seeds are added to the synthesis mixture, the framework type of the seeds can be the same or different from the molecular sieve obtained by the present method, for example from a different synthesis or from a previous synthesis, and can be suitably present in an amount of about 0.01 ppm by weight to about 10,000 ppm by weight based on the synthesis mixture, for example about 100 ppm by weight to about 5,000 ppm by weight of the synthesis mixture.
[0047] The synthesis mixture typically comprises water in a HO / Si molar ratio of 1 to 100, such as 4 or 5 to 80 or 70 or 50, such as 4 or 5 to 30 or 20. More particularly, in the first embodiment described above, the synthesis mixture may comprise water in a HO / Si molar ratio of 1 to 100, such as 4 to 80 or 5 to 70, such as 10 to 80 or 20 to 70, such as 20, 25 or 30, while in the second or third embodiment described above, the synthesis mixture may comprise water in a HO / Si molar ratio of 1 to 100, such as 2 to 50 or 3 to 30, such as 3 to 20 or 4 to 15, such as 4 to 10. Depending on the nature of the components in the base mixture, the amount of solvent (e.g., water from the hydroxide solution, and optionally methanol and ethanol from the hydrolysis of the silica source) in the base mixture may be removed to achieve the desired solvent to Si molar ratio for the synthesis mixture. Suitable methods for reducing solvent content can include evaporation under a static or flowing atmosphere, such as evaporation under ambient air, dry nitrogen, dry air, or evaporation by spray drying or freeze drying. When excessive water is removed during the solvent removal process, water can also be added to the resulting mixture to achieve the desired H2O / Si molar ratio. In some instances, when the preparation has a sufficient H2O / Si molar ratio, removal of water is not necessary.
[0048] Carbon in the form of CH2 may be present in a variety of sources of components used to prepare the synthesis mixture of the present disclosure, such as a silica source or a trivalent element source, and introduced as a bridging atom into the resulting molecular sieve framework. After SDA has been removed, nitrogen atoms may be introduced as bridging atoms into the framework of the molecular sieve material.
[0049] In one or more aspects, the synthesis mixture after solvent adjustment (e.g., wherein a desired water to silica ratio is achieved) can be mixed by mechanical processing such as stirring or high shear blending to ensure proper homogenization of the base mixture, for example, using dual asymmetric centrifugal mixing (e.g., FlackTek Speedmixer) at a mixing speed of 1000 rpm to 3000 rpm (e.g., 2000 rpm).
[0050] The synthesis mixture is then subjected to crystallization conditions suitable for the formation of molecular sieve materials. Crystallization of molecular sieve materials can be carried out under static or stirred conditions in a suitable reaction vessel, for example, in a convection oven maintained at an appropriate temperature. The autoclave is lined with stainless steel.
[0051] The crystallization in step (b) of the method is usually carried out at a temperature of 100°C to 200°C, such as 120°C to 180°C, such as 160°C or 170°C, for a time sufficient for crystallization to occur at the temperature used. For example, at a higher temperature, the crystallization time can be shortened. For example, the crystallization conditions in step (b) of the method may include heating for a time of 1 day to 100 days, such as 1 day to 50 days, such as 1 day to 30 days, such as at least 1 day or at least 5 days up to 30 days or 20 days. The crystallization time can be determined by methods known in the art, such as by sampling the synthesis mixture at different times and determining the yield and X-ray crystallinity of the precipitated solid. Unless otherwise specified herein, the temperature measured is the temperature of the surrounding environment of the material being heated, such as the temperature of the atmosphere in which the material is heated.
[0052] Typically, the molecular sieve is formed in solution and can be recovered by standard methods, such as by centrifugation or filtration. The separated molecular sieve can also be washed, recovered by centrifugation or filtration, and dried.
[0053] The molecular sieves of the present disclosure can be at least partially dehydrated (e.g., dried) when used as adsorbents or as catalysts in organic compound conversion processes. This can be accomplished by heating to a temperature in the range of 80° C. to 500° C., e.g., 90° C. to 370° C., for 30 minutes to 48 hours in an atmosphere such as air, nitrogen, etc., and at atmospheric pressure, subatmospheric pressure, or superatmospheric pressure. Dehydration can also be performed at room temperature simply by placing the molecular sieve in a vacuum, but a longer time is required to obtain a sufficient amount of dehydration.
[0054] As a result of the crystallization process, the recovered product contains at least a portion of the structure directing agent used in the synthesis in its pores. Therefore, the molecular sieve as-synthesized recovered from step (c) can be subjected to heat treatment or other treatment to remove part or all of the SDA introduced into its pores during the synthesis. The heat treatment (e.g., calcination) of the molecular sieve as-synthesized is generally subjected to a high temperature treatment sufficient to remove part or all of the SDA in a furnace in an atmosphere selected from air, nitrogen, ozone or a mixture thereof. Although a gas pressure lower than atmospheric pressure can be used for heat treatment, atmospheric pressure is desirable for convenience reasons. The heat treatment can be carried out at a temperature of up to 925°C, such as 300°C to 700°C or 400°C to 600°C. The measured temperature is the temperature of the surrounding environment of the sample. The heat treatment (e.g., calcination) can be carried out in a box furnace in dry air, which has been exposed to a drying tube containing a desiccant for removing water from the air. The heating is generally calcined for at least 1 minute, and is generally not more than 1 day or at most a few days. Heating may be performed first under a nitrogen atmosphere, and then the atmosphere may be switched to air and / or ozone.
[0055] The molecular sieve can also be subjected to ion exchange treatment, for example, using an aqueous ammonium salt solution such as ammonium nitrate, ammonium chloride, and ammonium acetate for ion exchange treatment, so as to remove the remaining alkali metal cations and / or alkaline earth metal cations if present in the synthesis mixture and replace them with protons, thereby producing a molecular sieve in acid form. To the desired extent, the original cations of the as-synthesized material, such as alkali metal cations, can be replaced by ion exchange with other cations. Preferred replacement cations can include hydrogen ions, hydrogen precursors such as ammonium ions, and mixtures thereof. The ion exchange step can be carried out after the as-synthesized molecular sieve is dried. The ion exchange step can be carried out before or after the calcination step.
[0056] Other treatments can also be carried out on the molecular sieve, such as steam treatment and / or washing with a solvent. Such treatments are well known to those skilled in the art and are used to improve the properties of the desired molecular sieve.
[0057] In a second aspect, the present disclosure relates to a molecular sieve, and more particularly to a molecular sieve of the CON framework type, which has at least one 1,2,3,4,6,7,8,9-octahydropyridazino[1,2-a]indazol-10- cation
[0058]
[0059] in its pore structure. The molecular sieve can be an aluminosilicate or an aluminoborosilicate and can be represented by the chemical formula of Formula 2:
[0060] (q)Q:(m)Al2O3:(n)B2O3:SiO2 (Formula 2),
[0061] where 0 < q ≤ 1.0, 0.005 < m ≤ 0.1, 0 ≤ n ≤ 0.1, and Q is the 1,2,3,4,6,7,8,9-octahydropyridazino[1,2-a]indazol-10- cation. The oxygen atoms in Formula 2 can be replaced by carbon atoms (e.g., in the form of CH2), and the carbon atoms can come from the source of the components used to prepare the as-synthesized molecular sieve. The oxygen atoms in Formula 2 can also be replaced by nitrogen atoms, for example, after the SDA has been removed. Formula 2 can represent the framework of a conventional molecular sieve having a structure-directing agent (Q) in its pore structure, but it does not mean that it is the only representative of such materials. The molecular sieve material can contain impurities not considered in Formula 2. In addition, Formula 2 does not include the protons and charge-compensating ions that may be present in the molecular sieve material.
[0062] The variable m represents the molar ratio relationship of Al2O3 to SiO2 in Formula 2. For example, when m is 0.005, the molar ratio of SiO2 to Al2O3 is 200, and the Si / Al molar ratio is 100. m can vary from 0.005 to 0.1, such as from 0.007 to 0.1, such as from 0.01 to 0.05, or from 0.015 to 0.05. The molar ratio of Si to Al can be 5 to 100, in particular 5 to 75, such as 10 to 50, such as 10 to 35.
[0063] The variable n represents the molar ratio relationship of B2O3 to SiO2 in Formula 2. When n is 0, boron is not present and the molecular sieve is an aluminosilicate. When n is greater than 0, boron is present and the molecular sieve is an aluminoborosilicate. For example, when n is 0.005, the molar ratio of SiO2 to B2O3 is 200, and the Si / B molar ratio is 100. When boron is present, n can vary from 0.005 to 0.1, such as from 0.007 to 0.1, such as from 0.01 to 0.05, or from 0.015 to 0.05. When boron is present, the molar ratio of Si to B can be 5 to 100, particularly 5 to 75, such as 10 to 50, such as 10 to 35.
[0064] The variable q represents the molar relationship of Q to SiO2 in Formula 2. For example, when n is 0.1, the Q / Si molar ratio is 0.1. The molar ratio of Q to SiO2 can be 0 to 1.0, such as 0.01 to 0.8, or 0.02 to 0.7, such as 0.1 to 0.5.
[0065] In another aspect, the present disclosure relates to a CON framework-type molecular sieve, which is obtainable by (or is obtained by) the method disclosed herein.
[0066] The molecular sieve material, particularly when prepared in the presence of hydroxide ions, may have an X-ray diffraction pattern in its as-synthesized form (e.g., wherein SDA has not been removed) and / or in its calcined form (e.g., wherein at least a portion of SDA has been removed) similar to the X-ray diffraction pattern of SSZ-26 zeolite (containing about 15% polymorph A) as disclosed in Tables 3 and 5, respectively, of U.S. Pat. No. 10,730,757, which is incorporated herein by reference in its entirety. When prepared in the presence of fluoride ions, the molecular sieve material may have an X-ray diffraction pattern in its as-synthesized form (e.g., wherein SDA has not been removed) and / or in its calcined form (e.g., wherein at least a portion of SDA has been removed) similar to the X-ray diffraction pattern of SSZ-33 zeolite (containing about 30% polymorph A) as disclosed in Tables 1(a) and 1(b), respectively, of U.S. Pat. No. 4,963,337, which is incorporated herein by reference in its entirety.
[0067] It will be appreciated by those skilled in the art that the molecular sieves obtainable by the methods disclosed herein may contain impurities, such as amorphous materials, unit cells with different topological structures (e.g., quartz or molecular sieves of different framework types, which may or may not affect the performance of the resulting catalyst) and / or other impurities (e.g., heavy metals and / or organic hydrocarbons). Typical examples of molecular sieves of different framework types coexisting with the molecular sieves of the present invention are molecular sieves of MTW, BEA, FAU or MOR framework types, such as ZSM-12, zeolite beta, undissolved faujasite or mordenite. The molecular sieves of the present invention are preferably substantially free of impurities. As used herein, the term "substantially free of impurities" (or alternatively "substantially pure") means that the molecular sieve material contains a small proportion (less than 50 wt%), preferably less than 20 wt%, more preferably less than 10 wt%, even more preferably less than 5 wt%, most preferably less than 1 wt% (e.g., less than 0.5 wt% or 0.1 wt%) of such impurities (or "non-CON" framework-type" materials), with the weight percentage (wt%) values being based on the combined weight of the impurities and the pure molecular sieve. The amount of impurities can be suitably determined by powder XRD, rotating electron diffraction and / or SEM / TEM (e.g., different crystal morphologies).
[0068] The molecular sieves obtainable by the methods described herein are substantially crystalline. As used herein, the term "crystallization" refers to the crystalline solid form of a material, including but not limited to single-component or multi-component crystal forms, such as solvates, hydrates, and eutectics. Crystallization can refer to molecules with regular repetition and / or orderly arrangement, and have distinguishable lattices. For example, molecular sieves can have different water contents or solvent contents. Different crystallization lattices can be determined by solid-state characterization methods, such as by XRD (e.g., powder XRD). Other characterization methods known to those of ordinary skill in the relevant art can further contribute to determining the crystalline form and to determining stability and solvent / water content. As used herein, the term "substantially crystalline" refers to that the majority (greater than 50% by weight) of the sample of the material described is crystalline, and the remainder of the sample is amorphous. In one or more aspects, a substantially crystalline sample has at least 95% crystallinity (e.g., 5% amorphous form), at least 96% crystallinity (e.g., 4% amorphous form), at least 97% crystallinity (e.g., 3% amorphous form), at least 98% crystallinity (e.g., about 2% amorphous form), at least 99% crystallinity (e.g., 1% amorphous form), and 100% crystallinity (e.g., 0% amorphous form).
[0069] Aspects of the present disclosure are described in more detail by way of specific embodiments. The following examples are provided for illustrative purposes only and are not intended to limit the present disclosure in any way. Those skilled in the relevant art will readily recognize that multiple parameters can be changed or modified to obtain substantially the same results.
[0070] Example
[0071] The following further illustrates the present disclosure but does not limit its scope.
[0072] In these examples, X-ray diffraction (XRD) patterns of the as-synthesized and calcined materials were recorded on an X-ray powder diffractometer (Bruker DaVinci D8 Discovery instrument) in continuous mode using Cu Kα radiation, a Vantec 500 detector in Bragg-Bentano geometry, over a 2θ range of 4 to 36 degrees. The interplanar spacings, d-spacings, were calculated in angstroms, while the relative intensities of the lines, I / I o is the ratio of the peak intensity above the background to the intensity of the strongest line. The intensity is not corrected for Lorentz and polarization effects. The position of the diffraction peak in 2θ and the relative peak area intensity of the line I / I( o ), where I o Is the intensity of the strongest line above the background. It should be understood that the diffraction data listed as a single line can be composed of multiple overlapping lines, which can appear as resolved or partially resolved lines under specific conditions such as differences in crystallographic changes. Typically, crystallographic changes can include slight changes in unit cell parameters and / or changes in crystal symmetry, while framework connectivity does not change. These slight effects, including changes in relative intensity, can also occur due to differences in cation content, framework composition, nature and degree of hole filling, crystal size and shape, preferred orientation, and thermal history and / or hydrothermal history.
[0073] The scanning electron microscope (SEM) images of the original material after synthesis were obtained on a Hitachi 4800 scanning electron microscope. The SEM images are used to help assess product purity. The presence of significantly different crystal forms in the SEM images may be an indication of impurities in the form of other crystalline materials. This approximate analysis may be particularly useful in determining the presence of relatively small amounts of crystalline impurities that are not determinable on the product XRD pattern.
[0074] The following measurements were performed on ion exchanged (when alkali metals were present in the synthesis mixture) and calcined samples. For each sample subjected to ion exchange and calcination, the following procedure was used: the as-prepared sample was calcined at 560°C for 8 hours to remove SDA, then ion exchanged twice with 1 M ammonium nitrate solution, and then calcined at 500°C for 4 hours.
[0075] The total BET surface area of the material (S BET ) is determined by the BET method using nitrogen adsorption-desorption at liquid nitrogen temperature as described by S. Brunauer, P. H. Emmett and E. Teller in J. Am. Chem. Soc., 1938, Vol. 60, p. 309, which is incorporated herein by reference. The external surface area (S) of a material is 外 ) was obtained by the t-plot method.
[0076] The micropore volume of the material (V 微 ) can be determined using methods known in the relevant art. For example, the micropore volume of a material can be measured using nitrogen physical adsorption, and the data can be analyzed using the t-plot method described in Lippens, BC et al., "Studies on pore systems in catalysts: V. The t method", J. Catal., Vol. 4, p. 319 (1965), which describes the micropore volume method and is incorporated herein by reference.
[0077] The alpha value is a measure of the catalyst cracking activity and is described in U.S. Pat. No. 3,354,078 and Journal of Catalysis, Vol. 4, p. 527 (1965); Vol. 6, p. 278 (1966); and Vol. 61, p. 395 (1980), each of which is incorporated herein by reference. The experimental conditions for the tests used herein include a constant temperature of 538° C. and a variable flow rate as described in detail in Journal of Catalysis, Vol. 61, p. 395.
[0078] Example 1 :1,2,3,4,6,7,8,9-octahydropyridazine[1,2-a]indazole-10- Synthesis of Hydroxides
[0079] To a solution of 20 g of 4,5,6,7-tetrahydroindazole in acetonitrile (250 mL) was added 45 g of K2CO3. After stirring at ambient temperature for 30 minutes, 70 g of 1,4-dibromobutane was added. The reaction mixture was stirred at ambient temperature for about 4 hours and then warmed to 90 ° C for about 24 hours. The mixture was then cooled to ambient temperature and the solvent was evaporated under reduced pressure. The residue was dissolved in dichloromethane and the resulting suspension was filtered. The solvent was removed in vacuo to obtain a mixture with 1,2,3,4,6,7,8,9-octahydropyridazine [1,2-a] indazole-10- The solid corresponding to the bromide.
[0080] The vacuum dried bromide salt is then reacted with an ion exchange resin IRN78OH hydroxide form was ion exchanged to the hydroxide form with a bromide:resin:water weight ratio of 1:3.5:5. The exchange was performed overnight at room temperature.
[0081] The molar ratios and conditions used for the synthesis of Examples 2-13 are detailed later and summarized in Table 2.
[0082] Example 2 : Synthesis of CON framework type molecular sieve (Si / Al=15) from USY zeolite in the presence of NaOH
[0083] In a PTFE liner of a 23 mL steel Parr autoclave, the following were mixed together: 1.90 g of SDAOH solution (13.9 wt %), 1.35 g of sodium hydroxide (NaOH, 4 wt %), 1.10 g of deionized water, and 0.64 g of Ultrastable Y (USY) zeolite with a Si / Al molar ratio of 15 (available from Zeolyst as CBV720) to produce a synthetic mixture having the following composition in molar ratio:
[0084] 25H2O: 1SiO2: 0.033Al2O3: 0.15SDAOH: 0.15NaOH.
[0085] The liner was then covered, sealed in a 23 mL Parr autoclave, and placed on a rack inside a convection oven. The reactor was heated at 160° C. under tumbling conditions (about 30 rpm) for 10 days. The as-synthesized material was isolated by filtration, rinsed with deionized water, and dried in a ventilated drying oven at 90° C.
[0086] XRD analysis of the as-synthesized product showed that the material had a CON framework type. Figure 1 Shown is the powder XRD pattern of the as-synthesized material. Figure 2 Shown is a SEM image of the as-synthesized material.
[0087] XRF analysis of the calcined and ion exchanged material indicated that the Si / Al molar ratio of the zeolite product was 21.
[0088] The BET specific surface area (S BET ) is 609m 2 / g, its external surface area (S 外 ) is 92m 2 / g, its micropore volume (V 微 ) is 0.22cc / g, and its α value is 1600. The observed micropore volume and specific surface area (S BET ) is consistent with the values reported for CON framework-type zeolites, which also indicates that the current structure-directing agents are able to drive complete crystallization.
[0089] The absorption of n-hexane, 2,2-dimethylbutane (2,2-DMB) and 2,3-dimethylbutane (2,3-DMB) on the ion-exchanged and calcined material was determined. The material was placed under a nitrogen stream, and then hydrocarbons were introduced through a sparger to saturate the nitrogen stream, and the hydrocarbon absorption was determined. Each hydrocarbon was adsorbed at different temperatures: n-hexane was adsorbed at 90°C, 2,2-DMB was adsorbed at 120°C, and 2,3-DMB was adsorbed at 120°C. The absorption of n-hexane was 133 mg / g, the absorption of 2,2-DMB was 141 mg / g, and the absorption of 2,3-DMB was 142 mg / g.
[0090] Example 3 : Synthesis of CON framework type molecular sieve (Si / Al=16) from silica and USY zeolite in the presence of NaOH
[0091] This example was conducted under similar conditions to Example 2, except that silica was used in combination with USY zeolite in the presence of a higher amount of water. In a 23 mL steel Parr autoclave with PTFE liner, the following materials were mixed together: 2.17 g of SDAOH solution (13.9 wt%), 0.52 g of Cab-O- M5 (medium surface fused silica available from Spectrum Chemical), 1.54 g of sodium hydroxide (NaOH, 4 wt%), 2.16 g of deionized water, and 0.19 g of Ultrastable Y (USY) zeolite having a Si / Al molar ratio of 2.5 (available from Zeolyst as CBV500) were added to produce a synthetic mixture having the following composition in molar ratio:
[0092] 30H2O: 1SiO2: 0.031Al2O3: 0.15SDAOH: 0.15NaOH.
[0093] The liner was then covered, sealed in a 23 mL Parr autoclave, and placed on a rack inside a convection oven. The reactor was heated at 160° C. under tumbling conditions (about 30 rpm) for 18 days. The as-synthesized material was isolated by filtration, rinsed with deionized water, and dried in a ventilated drying oven at 90° C.
[0094] This material had an XRD pattern similar to that of the as-synthesized material of Example 2. Figure 3 Shown is a SEM image of the as-synthesized material.
[0095] Example 4 : Synthesis of CON molecular sieve (Si / Al=16) from silica and USY zeolite in the presence of NaOH
[0096] This example was carried out under similar conditions as Example 4, except that the synthesis mixture contained a lower amount of NaOH and a higher amount of SDAOH, thereby producing a synthesis mixture having the following composition in molar ratio:
[0097] 30H2O: 1SiO2: 0.031Al2O3: 0.2SDAOH: 0.1NaOH.
[0098] After heating at 160°C for 18 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0099] Example 5 : Synthesis of CON framework type molecular sieve (Si / Al=25) from colloidal silica and sodium aluminate in the presence of NaOH
[0100] This example was carried out under similar conditions to the previous example, but the synthesis mixture contained HS40 (40 wt. % colloidal silica suspension) was used as a source of Si, and sodium aluminate (NaAlO2, 25 wt. % Al2O3, 19.3 wt. % Na2O) was used as a source of Al. The synthesis mixture had the following composition in molar ratio:
[0101] 25H2O: 1SiO2: 0.02Al2O3: 0.15SDAOH: 0.1NaOH.
[0102] After heating at 160°C for 18 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0103] Example 6 : Synthesis of CON framework type molecular sieve (Si / Al=20) from colloidal silica and sodium aluminate in the presence of NaOH
[0104] This example was carried out under similar conditions as Example 6, but the molar ratio of the synthetic mixture was slightly different:
[0105] 30H2O: 1SiO2: 0.02Al2O3: 0.2SDAOH: 0.1NaOH.
[0106] After heating at 160°C for 18 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0107] Example 7 : Synthesis of CON framework type molecular sieve (Si / Al=16) from colloidal silica and aluminum hydroxide in the presence of KOH
[0108] This example was carried out under similar conditions to the previous example, but the synthesis mixture contained HS40 (40 wt % colloidal silica suspension) as a source of Si, aluminum hydroxide (Al(OH)3, Sigma, 54 wt % Al2O3) as a source of Al, and potassium hydroxide (KOH, 20 wt %). The synthesis mixture has the following composition in molar ratio:
[0109] 30H2O: 1SiO2: 0.031Al2O3: 0.15SDAOH: 0.15KOH.
[0110] After heating at 160°C for 18 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0111] Example 8 : Synthesis of CON framework type molecular sieve (Si / Al=15) from colloidal silica and aluminum hydroxide in the presence of KOH
[0112] This example was carried out under similar conditions as Example 7, but the synthetic mixture had the following composition in molar ratio:
[0113] 25H2O: 1SiO2: 0.033Al2O3: 0.15SDAOH: 0.15KOH.
[0114] After heating at 170°C for 10 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0115] Example 9 : Synthesis of CON framework type molecular sieve (Si / Al=10) from colloidal silica and aluminum hydroxide in the presence of KOH
[0116] This example was carried out under similar conditions as Example 9, but the synthesis mixture contained a higher amount of Al. The synthesis mixture had the following composition in molar ratio:
[0117] 25H2O: 1SiO2: 0.05Al2O3: 0.15SDAOH: 0.15KOH.
[0118] After heating at 170°C for 10 days, a molecular sieve of CON framework type was obtained, which had an XRD pattern similar to that of the as-synthesized material of Example 2.
[0119] Example 10 : Synthesis of CON framework type molecular sieve (Si / Al=33) from TEOS and aluminum hydroxide in the presence of HF
[0120] In a PTFE-lined 23 mL steel Parr autoclave, 4.75 g of SDAOH solution (13.9 wt%), 1.41 g of tetraethyl orthosilicate (TEOS, >99 wt%) and 0.019 g of aluminum hydroxide (Al(OH)3, 54 wt%, Sigma) were stirred at room temperature for 3 hours and then heated to 60°C to remove 1.24 g of ethanol and 3.45 g of H2O. Finally, 0.14 g of HF (48 wt% solution) was added to the colloid to produce a synthetic mixture having the following composition in molar ratio:
[0121] 4H2O: 1SiO2: 0.015Al2O3: 0.5SDAOH: 0.5HF.
[0122] The liner was then capped, sealed in a 23 mL Parr autoclave, and placed on a rack inside a convection oven and heated at 160° C. under tumbling conditions (about 30 rpm) for 16 days. The resulting as-synthesized material was confirmed to be a CON framework-type molecular sieve, having an XRD pattern similar to that of the as-synthesized material of Example 2, plus a small amount of an impurity phase confirmed to be zeolite beta.
[0123] Embodiment 11 : Synthesis of CON framework type molecular sieve (Si / Al=17) from TEOS and aluminum hydroxide in the presence of HF
[0124] This example was carried out under similar conditions as Example 11, but the synthesis mixture contained a higher amount of Al. The synthesis mixture had the following composition in molar ratio:
[0125] 4H2O: 1SiO2: 0.029Al2O3: 0.5SDAOH: 0.5HF.
[0126] After heating at 160°C for 9 days, Figure 4 and Figure 5 As shown, XRD analysis of the as-synthesized product and the calcined product showed that the material has a CON framework type.
[0127] Example 12 : Synthesis of CON framework type molecular sieve (Si / Al=30, Si / B=20) from USY zeolite and boric acid in the presence of KOH
[0128] In a PTFE liner of a 23 mL steel Parr autoclave, the following were mixed together: 1.98 g of SDAOH solution (9.8 wt %), 0.36 g of potassium hydroxide (KOH, 20 wt %), 1.9 g of deionized water, 0.69 g of H3BO3 (3.9 wt %), and 0.54 g of Ultrastable Y (USY) zeolite with a Si / Al molar ratio of 30 (available from Zeolyst as CBV760) to produce a synthetic mixture having the following composition in molar ratio:
[0129] 30H2O: 1SiO2: 0.0167Al2O3: 0.025B2O3: 0.15SDAOH: 0.15KOH.
[0130] The liner was then covered, sealed in a 23 mL Parr autoclave, and placed on a rack inside a convection oven. The reactor was heated at 170°C under tumbling conditions (about 30 rpm) for 12 days. The as-synthesized material was isolated by filtration, rinsed with deionized water, and dried in a ventilated drying oven at 90°C. Figure 6 As shown, XRD analysis of the as-synthesized product showed that the material had a CON framework type.
[0131] Embodiment 13 : Synthesis of CON framework type molecular sieve (Si / Al=30, Si / B=33) from USY zeolite and boric acid in the presence of KOH
[0132] In a 23 mL steel Parr autoclave with a PTFE liner, the following materials were mixed together: 1.98 g of SDAOH solution (9.8 wt %), 0.36 g of potassium hydroxide (KOH, 20 wt %), 2.16 g of deionized water, 0.41 g of H3BO3 (3.9 wt %), and 0.54 g of Ultrastable Y (USY) zeolite with a Si / Al molar ratio of 30 (available from Zeolyst as CBV760), thereby producing a synthetic mixture having the following composition in molar ratio: 30H2O:1SiO2:0.0167Al2O3:0.015B2O3:0.15SDAOH:0.15KOH.
[0133] The liner was then covered, sealed in a 23 mL Parr autoclave, and placed on a rack inside a convection oven. The reactor was heated at 170 ° C for 12 days under tumbling conditions (about 30 rpm). The as-synthesized material was separated by filtration, rinsed with deionized water, and dried in a ventilated drying oven at 90 ° C. It was confirmed that the as-synthesized material obtained was a CON framework-type molecular sieve, which had an XRD pattern similar to the XRD pattern of the as-synthesized material of Example 12.
[0134] Table 2
[0135]
[0136] Although the present invention has been described and illustrated with reference to specific embodiments, it will be appreciated by those skilled in the art that the present invention may make many different changes, modifications and variations that are not specifically described herein. It is also clear to those skilled in the art that when numerical lower limits and numerical upper limits are listed herein, the range from any lower limit to any upper limit is considered. In addition, all numerical values in the specific embodiments herein are modified with "about" to specify values, and experimental errors and variations that should be expected by those skilled in the art are considered.
[0137] If integers or elements with known, obvious or foreseeable equivalents are mentioned in the foregoing description, such equivalents are also incorporated herein individually. The true scope of the present invention should be determined with reference to the claims, and should be understood to encompass any such equivalents. The reader should also understand that integers or features of the present invention described as preferred, advantageous, convenient forms, etc. are optional and do not limit the scope of the independent claims. In addition, it should be understood that such optional integers or features, although they may be beneficial in some embodiments of the present invention, may not be desired in other embodiments, and therefore may not exist.
[0138] Additionally or alternatively, the present invention relates to:
[0139] Embodiment 1: A method for preparing a CON framework type molecular sieve, the method comprising:
[0140] (a) preparing a synthesis mixture, the synthesis mixture comprising water, a source of silicon dioxide, a source of aluminum oxide, a structure directing agent (Q), a mineralizer, and optionally a source of an alkali metal and / or alkaline earth metal element (M), wherein the mineralizer is selected from the group consisting of hydroxide ions (OH), fluoride ions (F), and mixtures thereof, and wherein the structure directing agent (Q) comprises 1,2,3,4,6,7,8,9-octahydropyridazin[1,2-a]indazole-10- cation:
[0141]
[0142] (b) heating the synthesis mixture under crystallization conditions comprising a temperature of 100° C. to 200° C. for a time sufficient to form crystals of the molecular sieve; and
[0143] (c) recovering at least a portion of the molecular sieve from step (b).
[0144] Embodiment 2: The method according to embodiment 1, wherein the structure directing agent (Q) is in the form of a halide, a hydroxide or a nitrate, preferably wherein the structure directing agent (Q) is in the form of a hydroxide thereof.
[0145] Embodiment 3: The method according to embodiment 1 or 2, wherein the mineralizer comprises hydroxide ions (OH).
[0146] Embodiment 4: A method according to embodiment 3, wherein the source of hydroxide ions comprises at least one of the structure directing agent (Q) in the form of its hydroxide, sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonium hydroxide, preferably comprises the structure directing agent (Q) in the form of its hydroxide, sodium hydroxide and / or potassium hydroxide.
[0147] Embodiment 5: The method according to any one of the preceding embodiments, wherein the mineralizer comprises fluoride ions (F).
[0148] Embodiment 6: The method according to embodiment 5, wherein the source of fluoride ions comprises at least one of HF, NH4F and NH4HF2, preferably HF.
[0149] Embodiment 7: The method according to any one of the preceding embodiments, wherein the synthesis mixture has the following composition in molar ratio:
[0150]
[0151] Embodiment 8: The method according to any of the preceding embodiments, wherein the synthesis mixture further comprises a source of at least one boron oxide.
[0152] Embodiment 9: The method according to embodiment 8, wherein boron is present in the synthesis mixture in a Si / B molar ratio of 5 to 100, preferably 10 to 50, more preferably 10 to 35.
[0153] Embodiment 10: The method according to any one of the preceding embodiments, further comprising treating the molecular sieve recovered in step (c) to remove at least a portion of the structure directing agent (Q).
[0154] Embodiment 11: A molecular sieve having at least one 1,2,3,4,6,7,8,9-octahydropyridazino[1,2-a]indazol-10- in its pore structure cation.
[0155] Embodiment 12: The molecular sieve according to Embodiment 10, wherein the molecular sieve has a CON framework type.
[0156] Embodiment 13: The molecular sieve according to Embodiment 10 or 11, wherein the molecular sieve has the following formula 2:
[0157] (q)Q:(m)Al2O3:(n)B2O3:SiO2 (Formula 2),
[0158] where 0 < q ≤ 1.0, 0.005 < m ≤ 0.1, 0 ≤ n ≤ 0.1, and Q is 1,2,3,4,6,7,8,9-octahydropyridazino[1,2-a]indazol-10- of Formula 1 cation.
[0159] Embodiment 14: The molecular sieve according to any one of Embodiments 10 to 13, which can be obtained by the method according to any one of Embodiments 1 to 9.
Claims
1. A method for preparing a CON framework type molecular sieve, the method comprising: (a) preparing a synthesis mixture comprising water, a source of silicon dioxide, a source of aluminum oxide, a structure directing agent (Q), a mineralizer and optionally a source of an alkali metal and / or alkaline earth metal element (M), wherein the mineralizer is selected from hydroxide ions (OH), fluoride ions (F) and mixtures thereof, and The structure directing agent (Q) comprises 1,2,3,4,6,7,8,9-octahydropyridazine[1,2-a]indazole-10- cation: (b) heating the synthesis mixture under crystallization conditions including a temperature of 100° C. to 200° C. for a time sufficient to form crystals of the molecular sieve; as well as (c) recovering at least a portion of the molecular sieve from step (b).
2. The method according to claim 1, wherein the structure directing agent (Q) is in the form of a halide, hydroxide or nitrate, preferably wherein the structure directing agent (Q) is in the form of its hydroxide.
3. The method of claim 1 or 2, wherein the mineralizer comprises hydroxide ions (OH).
4. The method according to claim 3, wherein the source of hydroxide ions comprises at least one of the structure directing agent (Q) in the form of its hydroxide, sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonium hydroxide, preferably comprises the structure directing agent (Q) in the form of its hydroxide, sodium hydroxide and / or potassium hydroxide.
5. The method according to any one of the preceding claims, wherein the mineralizer comprises fluoride ions (F).
6. The method of claim 5, wherein the source of fluoride ions comprises at least one of HF, NH4F and NH4HF2, preferably HF.
7. The method according to any one of the preceding claims, wherein the synthesis mixture has the following composition in molar ratio:
8. The method according to any of the preceding claims, wherein the synthesis mixture further comprises a source of at least one boron oxide.
9. The process according to claim 8, wherein boron is present in the synthesis mixture in a Si / B molar ratio of 5 to 100, preferably 10 to 50, more preferably 10 to 35.
10. The process according to any one of the preceding claims, further comprising treating the molecular sieve recovered in step (c) to remove at least part of the structure directing agent (Q).
11. A molecular sieve having at least one 1,2,3,4,6,7,8,9-octahydropyridazin[1,2-a]indazole-10- cation. The molecular sieve according to claim 10 , wherein the molecular sieve has a CON framework type.
13. The molecular sieve according to claim 10 or 11, wherein the molecular sieve has the following formula 2: (q)Q: (m)Al2O3: (n)B2O3: SiO2 (Formula 2), in, 0 < q ≤ 1.0, 0.005 < m ≤ 0.1, 0 ≤ n ≤ 0.1, and Q is a 1,2,3,4,6,7,8,9-octahydropyridazino[1,2-a]indazol-10- cation.
14. The molecular sieve according to any one of claims 10 to 13, which is obtainable by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Synthesis of aluminosilicate zeolite SSZ-26 via interzeolite transformation
US10189717B2
Method for preparing SSZ-26 / 33 zeolites
US10730757B1
Catalytic conversion with a crystalline aluminosilicate activated with a metallic halide
US3354078A
Zeolite SSZ-26
US4910006A
Zeolite SSZ-33
US4963337A